(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes modern approaches to the study of cognitive units of language in the context of the Internet. Special attention is paid to the interaction of language and non-linguistic reality, which is typical for modern word semantics. The linguocultural approach emphasizes the anthropocentric and national-specific nature of language, whereas the cognitive approach seeks to integrate language into the general system of human cognitive mechanisms. The study also examines the communicatively significant components of knowledge that are involved in the speech meaning of language units through the situation and context, although they are not included in their systemic content. The Internet as a new medium of communication creates additional opportunities for studying these phenomena, contributing to a deep understanding of the processes of transformation of linguistic meanings and cognitive mechanisms in digital reality.